Physical fitness and anthropometric characteristics among adolescents living in urban or rural areas of Kosovo - Faton Tishukaj; Ismet Shalaj; Masar Gjaka; Besim Ademi; Rrustem Ahmetxhekaj; Norbert Bachl; Harald Tschan; Barbara Wessner (BMC, 2017)
Abstract Background High physical fitness levels in childhood and adolescence are associated with positive health-related outcomes later in life. Albeit many researchers investigated rural-urban differences in physical fitness, the outcomes of these studies are inconsistent and data on Kosovo are widely missing. Thus, this study aims to examine anthropometric and physical fitness parameters in 14 to 15 year old Kosovan adolescents living in rural and urban areas. Methods Two schools from Pristina (mostly urban population) and two schools in the surrounding villages of the district of Deçan (mostly rural population) were selected. Anthropometric and physical fitness parameters were determined from a total of 354 adolescents (216 urban: 14.5 ± 0.4 years, 138 rural: age 14.5 ± 0.4 years) who volunteered to participate in this cross-sectional study performed in 2013/14. Results The prevalence of overweight and obesity was 18.9% in girls and 28.2% in males and excess body fat was detected in 18.2% of the girls and 15.9% of the boys with no differences between rural and urban adolescents. Rural adolescents performed slightly better in relative handgrip strength (+4.7%, p = 0.032) and running speed (10 m: +2.2%, p = 0.012; 20 m: +1.9%, p = 0.035), but no other differences were detected in standing long jump, counter movement jump, cardiorespiratory fitness and sit and reach test. A multinomial logistic regression analysis revealed that being a female was associated with a lower relative risk for overweight (RR = 0.11, 95% CI: 0.03-0.34, p < 0.001) and high body fat content (RR = 0.20, 95% CI: 0.05-0.56, p < 0.001). In addition, higher handgrip strength, longer sprinting time and lower aerobic fitness were associated with a higher relative risk for overweight and excess body fat. In contrast, lower handgrip strength increased the risk for experiencing thinness (RR = 0.92, 95% CI: 0.89-0.96, p < 0.001). Conclusions It could be shown that there is a high prevalence of overweight and obesity, especially in 14 to 15 year old boys in Kosovo which does not differ between rural and urban areas. Worse physical performance is associated with a higher risk for overweight and obesity highlighting the importance for interventions in this area and for starting longitudinal observations of a secular trend.